1997
DOI: 10.1046/j.1365-2141.1997.1903004.x
|View full text |Cite
|
Sign up to set email alerts
|

The effects on growth and survival of IL‐6 can be dissociated in the U‐266‐1970/U‐266‐1984 and HL407E/HL407L human multiple myeloma cell lines

Abstract: Several studies have documented IL‐6‐dependent growth promotion of murine and human neoplastic plasma cells. However, it is well known that human multiple myeloma (MM) cells in vitro show a considerable degree of heterogeneity concerning growth and survival requirements. This heterogeneity, which probably reflects overlapping effects of feeder cells, interleukin 6 (IL‐6) and components of fetal calf serum (FCS) as well as tumour heterogeneity in vivo, has hampered the elucidation of molecular mechanisms underl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
13
0

Year Published

1999
1999
2011
2011

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 21 publications
4
13
0
Order By: Relevance
“…Both of these defects can result from the action of IL-6. Multiple previous studies have demonstrated that IL-6 can cause plasma cell proliferation (Jelinek et al, 1997;Klein et al, 1995;Lichtenstein et al, 1989;Ogata et al, 1997;Spets et al, 1997;Urashima et al, 1997;Westendorf et al, 1994Westendorf et al, , 1996. It has also been demonstrated that IL-6 and IGFs can protect myeloma cells from dexamethasone-induced apoptosis (Lichtenstein et al, 1995;Xu et al, 1997).…”
Section: Discussionmentioning
confidence: 98%
“…Both of these defects can result from the action of IL-6. Multiple previous studies have demonstrated that IL-6 can cause plasma cell proliferation (Jelinek et al, 1997;Klein et al, 1995;Lichtenstein et al, 1989;Ogata et al, 1997;Spets et al, 1997;Urashima et al, 1997;Westendorf et al, 1994Westendorf et al, , 1996. It has also been demonstrated that IL-6 and IGFs can protect myeloma cells from dexamethasone-induced apoptosis (Lichtenstein et al, 1995;Xu et al, 1997).…”
Section: Discussionmentioning
confidence: 98%
“…24 The MCCs included at least 98% plasma cells and were used at early passages; thus, they had biologic characteristics resembling those of freshly expanded myeloma cells. The 2 myeloma cell lines, IM-9 and U-266-1970 (early passage), 27,38 were used as controls for IL-6-independent and IL-6-dependent myeloma cell lines, respectively. 8…”
Section: Bmmc and Cell Culturesmentioning
confidence: 99%
“…Experimental evidence suggests that these 2 effects are dissociable and mediated by distinct signaling pathways. 27 Interaction of IL-6 with its ␣-chain receptor, gp80, induces homodimerization of gp130, the signal-transducing receptor component, as well as activation of different downstream pathways, such as activation of Stat-1, Stat-3, or Ras proteins, with subsequent activation of the kinase cascade that includes the mitogen-activated protein kinases (MAPK). [28][29] Activation of the MAPK cascade induces cell growth, whereas the Stat-3 pathway has an antiapoptotic effect.…”
mentioning
confidence: 99%
“…Experimental evidence suggests that these two effects are dissociable and mediated by distinct signalling pathways (Fukada et al , 1996; Ogata et al , 1997; Spets et al , 1997). Stat‐3 activation has an anti‐apoptotic effect (Fukada et al , 1996; Spets et al , 1997), and activation of Ras protein induces cell growth (Ogata et al , 1997). Furthermore, transfection of activated Ras‐complementary DNA into the IL‐6‐dependent ANBL6 myeloma cell line induced IL‐6‐independent cell growth and resistance to drug‐induced apoptosis (Billadeau et al , 1997), suggesting that Ras mutations may be related to autocrine IL‐6 production (Lubbert et al , 1993), myeloma cell growth and response to therapy (Billadeau et al , 1997).…”
mentioning
confidence: 99%